"Through the looking glass: envisioning new library technologies" educational trends that will impact library technology. Issue 1 (6th March 2017) - Fernandez, Peter
Abstract : Purpose: This column takes a big picture look at some of the technology-related trends in education to identify potential opportunities for libraries. Design/methodology/approach: In particular, it is inspired by the 2016 NMC Horizon Report, which attempts to identify and describe emerging technologies likely to have an impact on learning, teaching and creative inquiry in education. Findings: Although this report was created in the context of higher education, it impacts all libraries that support lifelong learning. In fact, some of the concepts considered in the report, such as digital literacy and makerspaces, are already well integrated into the operations of many libraries. Originality/value: This column's focus will be on the concepts of personalized learning, competing models of education and the blending of informal and formal learning, and it will examine how libraries can use related technologies to position themselves to best assist their patrons in the future.